Clinical spectrum of HLA-B27-associated ocular inflammation - Pyare, Richa; Majumder, Parthopratim Dutta (Nepalese Journal of Ophthalmology, 2022)
Introduction: HLA-B27-associated anterior uveitis is the most common identifiable cause of anterior uveitis in adults worldwide. It is associated with significant ocular morbidity in young patients due to its typically recurrent attacks of inflammation and vision-threatening ocular complications.Materials and methods: This review was compiled using articles identified by searching on PubMed with all relevant keywords such as HLA B27, HLA B27 uveitis, spondyloarthritis, Ankylosing spondylitis, HLA B27 systemic associations.Results: We summarize the current knowledge on the HLA B27 associated uveitis epidemiology, genetics, clinical profile, systemic associations, laboratory investigations, complications and management.Conclusion: HLA-B27-associated uveitis is a commonly encountered entity in the uveitic clinic. Its management must be in coordination with a rheumatologist. Early and appropriately intense treatment is essential for optimal visual prognosis.